Implementation of the Marketing Mix Clinic Fertility (IVF) Strategy with the Assurance System in the Kamala Clinic - Suharyati Shafiyyah; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Ratna Indrawati Lestariani (Journal of Multidisciplinary Academic, 2021)
Currently, Indonesia has many fertility clinic-based health facilities that provide various kinds of affordable price offers. The Kamala Clinic is present as one of the clinics that offers a success guarantee system for patients who want to have children or add children. The Kamala Clinic is a premier clinic that is a network of private clinics providing fertility and gynaecology services. The Kamala Clinic is under PT. Medika Sehat Utama and has committed to developing fertility and gynaecology clinics and as well as offering an in vitro fertilization (IVF) program with a guarantee (self-insurance). Thus, study aimed to discuss the application of the NICE concept (Networking, Interaction, Common Interest, Experience) on marketing mix strategy at the IVF clinic. Here we use a SWOT (Strength, Weakness, Opportunity, and Threat) analysis to achieve the result with assign Segmenting, Targeting, and positioning over classify the market. In addition, Marketing mix implementation at The Kamala Clinic is expected to optimize the company’s internal strengths and minimized threats from the outside. The results of this study are expected to apply the marketing concept so that it has superior, competitive, and profitable capabilities to become a new rule business model for other IVF clinics.